2024
DOI: 10.61707/1phztv11
|View full text |Cite
|
Sign up to set email alerts
|

The Differences between the Attorney General and The Corruption Eradication Commission in Prosecuting Corruption Cases in Indonesia: A Legal Analysis

Tofik Yanuar Chandra,
Bambang Slamet Riyadi

Abstract: Corruption cases are complicated since they involve a number of parties. The goal of this study is to comprehend the distinctions between the Corruption Eradication Commission and the Attorney in Indonesian corruption cases that are intriguing to examine from both a sociological and ontological perspective. Undertaking a legal normative analysis is an intriguing way to investigate the issue. Data were gathered by observation and documentation. Legal data analysis was used to analyze the data. The results indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
0
0
Order By: Relevance
“…There is a study examines white-collar crime in Indonesia during the reform period, focusing on state officials, parliament, and political parties, found that white-collar crime has reached alarming levels, potentially forming state organized (Chandra & Riyadi, 2024;Purboyo, Riyadi, Irawan, & Inkiriwang, 2024;B. Sl.…”
Section: Introductionmentioning
confidence: 99%
“…There is a study examines white-collar crime in Indonesia during the reform period, focusing on state officials, parliament, and political parties, found that white-collar crime has reached alarming levels, potentially forming state organized (Chandra & Riyadi, 2024;Purboyo, Riyadi, Irawan, & Inkiriwang, 2024;B. Sl.…”
Section: Introductionmentioning
confidence: 99%